Teachers’ Self-Efficacy in Virtual Classrooms : Experiences of Pakistani Teachers during the COVID-19 Pandemic - Momin Khoja, Samreen (My University, 2022)
The COVID-19 pandemic forced schools around the world to shift teaching from physical to virtual environments. Despite challenges, several Pakistani private schools opted for synchronous online teaching that compelled teachers to make necessary pedagogical changes and in absence of appropriate support, they turned to their self-efficacy beliefs. The current study, using the teachers’ self-efficacy integrated-cyclical model of Tschannen-Moran et al., (1998) driven by the self-efficacy conception of Bandura (1997), aimed to explore the role of self-efficacy beliefs, its sources, and collective efficacy in motivating teachers to continue teaching in virtual classrooms. Using qualitative research, a semi-structured interview was employed to understand the nuanced interpretations of sources of teachers’ self-efficacy. The findings, seen in the context of the pandemic, indicate that, in addition to the other three sources (mastery experience, vicarious experience, physiological and affective state), teachers heavily relied on the constructive feedback of mentors as social and verbal persuasion to maintain their efficacy beliefs. Moreover, collective efficacy significantly supported teachers in moving from individual to collaborative inquiry and reflective practice to achieve their shared goals. Teachers also indicated difficult personal circumstances, limited institutional support, and lack of learners’ motivation as some of the challenges that hinder teaching beliefs. The study recommends continuous professional development to enhance teachers’ knowledge about technology and pedagogical integration, training of teacher mentors, creating avenues for teachers’ learning communities, and institutional support during difficult times to boost teachers’ self-efficacy.
Keywords: COVID-19, teachers’ self-efficacy, sources of self-efficacy, virtual classroom, Pakistani secondary-school teachers, qualitative research